School enrolment and attendance - Department of Social Services (Department of Social Services, 2015)
This article uses 5 waves of the Longitudinal Study of Indigenous Children to examine enrolment and attendance patterns of Indigenous children in the study.
Footprints in Time: The Longitudinal Study of Indigenous Children: Report from Wave 5
Keywords: Children -- Indigenous; Education and Training -- Early Childhood; Learning, education and training; Children; Education and Training; Early Childhood; Indigenous; Learning, education and training